It’s all in your head: sinus node dysfunction secondary to a sphenoid wing meningioma - Rivinius, Rasmus; Darche, Fabrice Fernand; Campos, Benito; Unterberg, Andreas; Schweizer, Leonille; Thomas, Dierk; Katus, Hugo; Schweizer, Patrick Alexander (Herzschrittmachertherapie + Elektrophysiologie, 2015)
A 57-year-old man presented with recurrent episodes of dizziness, weakness of legs, and presyncope. The electrocardiogram showed a sinus bradycardia and recurrent sinus pauses.